Tribological behavior of Ti6Al4V cellular structures produced by Selective Laser Melting - Bartolomeu, F. (2017)
Additive manufacturing (AM) technologies enable the fabrication of innovative structures with complex geometries not easily manufactured by traditional processes. Regarding metallic cellular structures with tailored/customized mechanical and wear performance aiming to biomedical applications, Selective Laser Melting (SLM) is a remarkable solution for their production. Focusing on prosthesis and implants, in addition to a suitable Young's modulus it is important to assess the friction response and wear resistance of these cellular structures in a natural environment. In this sense, five cellular Ti6Al4V structures with different open-cell sizes (100–500 μm) were designed and produced by SLM. These structures were tribologicaly tested against alumina using a reciprocating sliding ball-on-plate tribometer. Samples were submerged in Phosphate Buffered Saline (PBS) fluid at 37 °C, in order to mimic in some extent the human body environment. The results showed that friction and wear performance of Ti6Al4V cellular structures is influenced by the structure open-cell size. The higher wear resistance was obtained for structures with 100 μm designed open-cell size due to the higher apparent area of contact to support tribological loading.